20 years of port reform in Brazil: Insights into the reform process. (March 2017) - Galvão, Cassia Bomer; Robles, Leo Tadeu; Guerise, Luciana Cardoso
Abstract: The Brazilian port reform took place in the context of the Brazilian state reform of the 1990s. This process, as expected, was permeated by conflicts, contradictions, and lengthy negotiations. Our goal is to assess the Brazilian port governance changes in the 1993–2013 period, and to identify the main issues related to its implementation, as diverse strategies were adopted. Considering Brazil's foreign trade profile and its role in the international market, the paper covers the period from 1993 to 2013, marked by the publication of two port reform laws, Law 8630 from February 1993 and Law 12815 from June 2013. The methodology is based on critical analysis of the legislation contents, as well as documents of the Special Committees of the National Congress, specialised reports, and reports by the media and interviews with experts. Our findings have identified advances and setbacks in the Brazilian governance model. The results point to a long and controversial process in the 1990s, mainly undertaken by businesses and workers, and, in 2013, by port operators in public ports and private terminals and by potential newcomers.